INOVASI DAKWAH PERGURUAN TINGGI (STUDI NARATIF PADA UNIVERSITAS NEGERI SEMARANG) - Noekent, Vitradesie Noekent; Kurniawan, Andri (Universitas Islam Negeri Mataram, 2020)
Innovation of da'wah in higher education serves the heart of a successful balance of academic achievement and the nobility of the academic community. This study aims to narrate the innovation of da'wah at the Universitas Negeri Semarang within the framework of da’wah management theory that prioritizes a contingency approach in creating a harmony of preaching and academic activities. The research method used was a narrative study of three key figures who created the da'wah ecosystem at Universitas Negeri Semarang. The results showed that the enthusiasm for preaching has gained momentum since the strengthening of the role and physics of mosques in all faculties in Universitas Negeri Semarang. The existence of the mosque gave birth to prominent figures, created a routine of preaching moderation, as well as eliminating the seeds of radicalism and intolerance in the campus environment. Furthermore, authors also provide suggestions for higher education leaders and the government (Kemendikbud) as the regulator of higher education in Indonesia.